Surgical stabilization of appendicular joints in tuberculous arthritis: its place in treatment of osteoarticular tuberculosis - V. S. Zubikov; E. O. Peretsmanas (Туберкулез и болезни лёгких)
The objective: to analyze results of stabilizing techniques in the surgical treatment of tuberculous arthritis of appendicular joints, to define their place in treatment of tuberculous arthritis.Subjects and Methods. Data of 8 patients who underwent surgery for tuberculosis of appendicular joints were analyzed during the study. 7 patients suffered from tuberculosis of rare localization: ankle – 3 cases, foot – 1 case, wrist – 3 cases. And 1 patient suffers from tuberculosis of the knee joint, underwent arthrodesis, which eventually failed, had quadriceps fibrosis with no patella. At the time of the study, athroplasty couldn’t be performed in all 8 patients, so stabilizing surgery including arthrodesis was the method of choice. With the active tuberculosis disease and an extensive bone defect of the joint in 5 patients, static cement spacers loaded with anti-tuberculosis drugs were used. Spacers were used both for two-stage surgical treatment (2 cases) and one-stage (3 cases).Results: in all 8 cases, the stable eradication of tuberculosis infection was achieved with a follow-up period from 6 months to 7 years, average duration of follow-up made 2.2 Ѓ} 1.4 years. In 5 patients with tuberculosis of the ankle, foot and former knee joint, the support ability of the extremity was restored. With the stabilization of the wrist in a functionally advantageous position, all 3 patients showed a significant improvement in hand functions. After the spacer was installed, all patients were scheduled for the second stage of the operation but 3 of them achieved a good functional result, thus it was possible to avoid the next stage. The main criterion for stabilizing surgery of joints may be the impossibility of performing arthroplasty in cases of extensive bone defects as well as in case of persistent loss of anatomical structures.